Gene bookmarking accelerates the kinetics of post-mitotic transcriptional re-activation - Zhao, Rui (2011)
Although transmission of the gene expression program from mother to daughter cells has been suggested to be mediated by gene bookmarking, the precise mechanism by which bookmarking mediates post-mitotic transcriptional re-activation has been unclear. Here, we used a real-time gene expression system to quantitatively demonstrate that transcriptional activation of the same genetic locus occurs with a significantly more rapid kinetics in post-mitotic cells versus interphase cells. RNA polymerase II large subunit (Pol II) and Bromodomain Protein 4 (BRD4) were recruited to the locus in a different sequential order upon interphase initiation versus post-mitotic re-activation resulting from the recognition by BRD4 of increased levels of histone H4 lysine 5 acetylation (H4K5Ac) on the previously activated locus. BRD4 accelerated the dynamics of mRNA synthesis by de-compacting chromatin and hence facilitating transcriptional reactivation. Together, using a real-time quantitative approach, we identified differences in the kinetics of transcriptional activation between interphase and post-mitotic cells that are mediated by a chromatin-based epigenetic mechanism.